Causes and consequences of state violence against civilians: The Rohingya of Myanmar - C. Austin Davis; Paula Lopez-Pena; Ahmed Mushfiq Mobarak; Jaya Y. Wen (Yale University, Economic Growth Center, 2023)
While the United Nations describes Myanmar's oppression of the Rohingya as "a textbook example of ethnic cleansing" (UN, 2017), the state maintains that the violence was idiosyncratic and not motivated by anti-Rohingya animus. We assemble existing and original large-sample data to evaluate these claims. First, we document systematic economic motives: violence against minority civilians increased in places suitable for rice cultivation when rice prices were high. Correspondingly, in an original representative survey of Rohingya refugees in Bangladesh we find substantial losses of agricultural land, inputs, and inventories. Next, using a vector auto-regression approach, we find that state violence was consistent with Rohingya-specific animus. The state attacked substantially more than the Rohingya militia, targeted civilians disproportionately relative to other ethnic conflicts in Myanmar, and leveraged nationalist religious ideology. Finally, we document high rates of trauma exposure and depression among Rohingya refugees. Together, these results strongly rebut the government's narrative and illustrate how quantitative tools can shed light on episodes of ethnic cleansing.
Keywords: 330